Principles of the Concept of Reverse Conversion to Substantiate the Use of Underground Metro Structures as Shelters - Tiutkin, O. L.; Bannikov, D. O.; Ostapenko, I. S.; Hernych, M. V. (Science and Transport Progress, 2025)
Purpose. The authors set the goal of determining the principles of the concept of reverse conversion to substantiate the use of underground metro structures as shelters for critical infrastructure facilities. Methodology. The article analyzes and classifies already constructed shelters, as well as dual-purpose facilities offered on the construction market of Ukraine. The features of protective structures, their design parameters, advantages and disadvantages are determined. It is noted that the emergence of new ideas and even the formation of concepts covering adjacent areas dedicated to shelters is associated with the development of the underground space of large cities, that is, with an area that has already been developed earlier. It is proven that the Ukrainian experience in the use of protective structures provides the opportunity to create a new concept in which already known designs of underground civil structures can successfully perform the role of shelters. Findings. To substantiate the use of underground structures as shelters for critical infrastructure facilities, a new concept has been introduced, which has been called “reverse conversion”. Reverse conversion is the process of transferring exclusively civilian design and technological solutions to the military sphere, as well as to the area close to it, namely the area of construction of protective structures. It is substantiated that a single-vaulted shallow metro station, built of monolithic reinforced concrete, and a column shallow metro station, assembled from precast reinforced concrete, have high potential as shelters. It is proven that design and technological solutions for the construction of underground metro structures (shallow stations) are transferred to the area of construction of protective structures, and are not used as dual-purpose facilities. Originality. The article first presents the principles of the concept of reverse conversion, which provides an opportunity to expand the space of solutions for creating protective structures. Practical value lies in in the substantiation of shallow subway stations as shelters for critical infrastructure facilities.